Oxygen Transport Kinetics of Mixed Ionic-Electronic Conductors by Coupling Focused Ion Beam Tomography and Electrochemical Impedance Spectroscopy. Issue 4 (1st January 2017) - Almar, Laura; Szász, Julian; Weber, André; Ivers-Tiffée, Ellen
Abstract : The oxygen reduction reaction of mixed ionic-electronic conducting (MIEC) cathodes Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF) and La0.58 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) is investigated by detailed electrochemical impedance spectroscopy and focused ion beam tomography. The oxygen transport parameters of these materials are usually determined for model systems, such as dense bulks or thin films. However in the present study, probable differences regarding the time and thermal history of the samples (e.g. ambient poisoning gases, grain coarsening, secondary phase or surface segregation, etc.) were avoided by the in situ sintering of electrodes with nominal stoichiometry under synthetic air. The microstructural parameters of the electrodes are obtained by 3D FIB-SEM reconstruction tomography and subsequently used in combination with the Adler-Lane-Steele analytical model to calculate a simulated cathode resistance. Large discrepancies are observed compared to the electrochemical impedance measurements. In particular, the electrochemical impedance measurements do not show a Gerischer behavior, as expected for MIEC materials controlled by a coupled surface-exchange and bulk diffusion. Analysis by distribution function of relaxation times (DRT) reveals four individual processes taking place, indicating a surface-exchange controlled behavior with a reaction zone similar to the particle size. Bulk diffusion (D) and surface-exchange (k) coefficients from literature are critically discussed and tentative surface-exchange coefficients (k) for both MIECs are given.